Prospects for legal education in Uzbekistan: my opinion and views - Juraeva, Muslima (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
In this article the author made an attempt through analysis and comparison with leading universities of the world to express his point of view about legal education in an accessible way, and also try to formulate his vision regarding the future of legal education in the Republic of Uzbekistan